Increasing Income of Micro, Small and Medium Enterprises through Managerial and Digital Marketing Aspect in West Java - Hernita, Nita; Prihartini, Endah; Rahmayani, Melia Wida (Budapest International Research and Critics University, 2021)
The economy of West Java is the highest supported by Micro, Small and Medium Enterprises (MSMEs). West Java has MSMEs engaged in the food sector. The Covid-19 pandemic condition has an impact on decreasing income. The income of UMKM will support by marketing and management aspects. Some MSMEs in the food sector are still unable to solve managerial problems, even if their products have not been marketed through online media. This research method is a survey research with a descriptive approach using narrative analysis tools. The population in this study was the food sector MSMEs in West Java, amounting to 2400 MSME partners selected through cluster random sampling technique. The results of the analysis show that the income of MSMEs in the food sector has decreased because it is support by managerial aspects which has a value of respondents of 1706 (important) and marketing aspects of 3005 (very important). The increase in income will balance with business digitization in the context of marketing and paying attention to managerial aspects.